Hydrogenation of iron in the early stage of Earth’s evolution - Riko Iizuka-Oku (Nature Portfolio, 2017)
The Earth’s core has lower density than pure iron and many studies have looked into which light elements may be present. The authors here carry outin situhigh pressure and temperature neutron experiments indicating that hydrogen may have been the first light element to dissolve into the iron core.